Secrets of the Anglo-Saxon goldsmiths: Analysis of gold objects from the Staffordshire Hoard. (August 2016) - Blakelock, Eleanor; La Niece, Susan; Fern, Chris
Abstract: The Staffordshire Hoard is the largest ever find of Anglo-Saxon gold and silver metalwork. The collection comprises many hundreds of objects, in approximately 3900 fragments. Most objects are fittings from swords, but there are also fragments from at least one helmet, and a small but significant collection of Christian objects. An initial study of 16 gold objects from the collection suggested that some form of deliberately induced depletion gilding had taken place to remove both silver and copper from the surface of the metal (Blakelock, In press). Subsequently, both surface and quantitative core alloy SEM-EDX analysis was undertaken on a further 114 Hoard objects. Over 222 individual components (i.e. different parts of objects) were analysed during this study. This is the largest quantitative survey of Anglo-Saxon gold and, contrary to expectations, no reliable relationship was found between the fineness of alloy used and object date, although the low copper content is consistent with the use of recycled coinage as a source of gold. However, over 100 components were judged to be deliberately depleted in silver at their surface which, it is argued, was the result of a deliberate and probably widespread Anglo-Saxon workshop practice. Previously unrecognised, this involved the depletion gilding of sheet gold to create contrast between decorative components, as well as to enhance colour. Furthermore, in the light of the identification of this systematic surface enrichment, similar approaches should be considered to investigate goldsmithing practices in other cultures and time frames. Highlights: Results from the study of gold objects from the Anglo-Saxon Staffordshire Hoard. The largest SEM-EDX study of Anglo-Saxon gold carried out to date. The probable identification of the surface treatment of gold as widespread in Anglo Saxon workshops. The results suggest that a similar approach could identify unrecognised workshop practices in other cultures.